Judgment of togetherness in performances by musical duos - D'Amario, Sara; Goebl, Werner; Bishop, Laura (Frontiers in Psychology, 2022)
Musicians experience varying degrees of togetherness with their co-performers when playing in ensembles. However, little is know\sara{n} about how togetherness is experienced by audiences and how interpersonal dynamics in body motion and sound support the judgment of togetherness. This research investigates audience sensitivity to audio and visual markers of interperformer coordination and expressivity in ensembles, in relation to modality of stimulus presentation and audience music background. A set of duo ensemble performances, comprising motion capture recordings of the musicians’ upper bodies and instruments, were presented to participants with varying music background, including novices and semi-professional musicians. Participants were required to: i) watch and listen, ii) only watch, and iii) only listen to the selected recordings, whilst providing dynamic ratings of how much togetherness between musicians they perceived. Results demonstrate that sound intensity and similarity in right arm motion (quantified using cross-wavelet transform analysis) were significant predictors of \sara{rated} togetherness in novices, whilst sound synchronization and chest motion coordination predicted togetherness responses in semi-professional musicians. These results suggest the relevance of the quality of body motion coordination and of certain features of the audio outputs in the audience perception of togetherness. This research contributes to a better understanding of the perceptual mechanisms supporting socio-cognitive judgments of joint action activities.